2020
DOI: 10.3390/nu12051218
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Psychosocial Impairment, Food Choice Motives, and Orthorexic Behaviors among Polish Adults

Abstract: Orthorexic behaviors correlate not only with health motives when choosing food but may also coexist with psychosocial impairment. The aim of this study was to assess the motives of food choice and psychosocial impairment among adults with orthorexic behaviors through the use of ORTO-15 and ORTO-7. The data for the study were collected from a sample of 1007 Polish adults through a cross-sectional quantitative survey conducted in 2019. The respondents were asked to complete the ORTO-15 questionnaire, the Food Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Correspondingly, a greater understanding of the factors that influence dietary patterns and diet quality in law enforcement personnel is needed to further inform potential interventions [ 18 ]. In particular, the identification of barriers to the consumption of healthy foods must be identified in the design of effective behaviour change interventions [ 19 21 ]. Law enforcement personnel are known to have a range of challenges including shift work, overtime, and lack of structured breaks due to their nature of their work [ 5 7 , 13 , 22 ] hence understanding their perception of barriers is useful.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, a greater understanding of the factors that influence dietary patterns and diet quality in law enforcement personnel is needed to further inform potential interventions [ 18 ]. In particular, the identification of barriers to the consumption of healthy foods must be identified in the design of effective behaviour change interventions [ 19 21 ]. Law enforcement personnel are known to have a range of challenges including shift work, overtime, and lack of structured breaks due to their nature of their work [ 5 7 , 13 , 22 ] hence understanding their perception of barriers is useful.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was a smaller study, possibly precluding detection of the associations observed herein. In fact, it is known that some eating motives are related to disordered eating attitudes among the general population . Although we found that levels of disordered eating were low, we were able to identify certain food choice motives that were associated with increased DEAS scores in vegans: “sociability,” “traditional eating,” “visual appeal,” “pleasure,” “social norms,” “social image,” “weight control,” and “affect regulation.” This aligns with previous research that shows that individuals more concerned with their appearance and social image, as well as emotional eaters, exhibit more disordered eating attitudes, while individuals who respect internal cues to eat (eg, hunger, satiety, desires) and have a non–weight related health concern tend to have a better relationship with their own bodies and healthier eating attitudes.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, a previous small-scale study (62 participants) that comprised vegan dieters mainly due to ethical reasons did not find a higher risk of eating disorder symptoms. 32 Moreover, eating motives commonly related to disordered eating attitudes (ie, weight control, affect regulation) 9,10 were not reported as important eating motives in our population. In fact, vegetarians (including vegans)…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations